Politics and political literacy in education from the perspective of the public - Štefan Karolčík; Juraj Steiner; Elena Čipková (Cogent Education)
If we expect students in the future to make confident, responsible, and informed decisions based on knowledge, understanding and respect, we cannot ignore politics and political rationale in the process of education. In our study, we present the results of a survey investigating the opinions and attitudes of a selected part of the Slovak adult population on the use of politics, political topics, and political discussion in the teaching process, specifically in geography education. The research was conducted in 2022 and involved 660 adult individuals from all regions of Slovakia. Our research confirmed the prevailing high degree of agreement with the inclusion of political topics and debates in the teaching process. Females are more likely than males to agree with the inclusion of political topics and political debates in the classroom. Respondents aged between 27 and 37 agreed strongly with the opinion that political discussions and debates on political topics belong to schools and that students should be exposed to them in the classroom.